Lingkungan Kerja dan Kompensasi: Kunci Meningkatkan Produktivitas Kerja - Amirudin, Ahmad (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
Employee work productivity is a crucial factor in determining the success of an organization. The work environment and compensation are two factors that can influence the productivity of employees. A comfortable and conducive work environment can boost employees' morale, while fair and competitive compensation can enhance their motivation. This research aims to investigate the impact of the work environment and compensation on employee work productivity. The study employs a quantitative method with an associative approach. The population of the research comprises all employees at PT Satya Dinamika Mandiri. The sample size is 105 individuals, and data are collected through a questionnaire. Regression analysis is utilized to analyze the data and identify causal relationships among variables. The research results indicate that the work environment and compensation, when considered simultaneously, significantly affect the work productivity of employees. The work environment has a greater influence on employee work productivity compared to compensation. Based on these findings, companies need to pay attention to both factors to enhance employee work productivity. It is crucial for organizations to create a comfortable and conducive work environment and provide fair and competitive compensation. This conclusion emphasizes the importance of companies in creating a conducive work environment and adequate compensation system to increase employee productivity and welfare. By understanding and managing these aspects, companies can design more effective human resource management strategies to achieve organizational goals optimally.